2004
DOI: 10.2214/ajr.182.2.1820419
|View full text |Cite
|
Sign up to set email alerts
|

MDCT in Pancreatic Adenocarcinoma: Prediction of Vascular Invasion and Resectability Using a Multiphasic Technique with Curved Planar Reformations

Abstract: Our preliminary data on MDCT show that the technique has excellent negative predictive value for vascular invasion and good negative predictive value for overall tumor resectability in patients with pancreatic adenocarcinoma, suggesting an improvement over previous results reported using single-detector CT. The problem of undetected micrometastases to the liver and peritoneum remains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
91
0
6

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 243 publications
(101 citation statements)
references
References 19 publications
4
91
0
6
Order By: Relevance
“…In general, carcinomas in the head, uncinate process and tail of pancreas mainly invade the right coelial plexus, superior mesentery artery (��A) nerve plexus and splenic plexus, respectively ��A) nerve plexus and splenic plexus, respectively nerve plexus and splenic plexus, respectively nerve plexus and splenic plexus, respectively [5][6][7]12] . It has been reported that the application of coronal and sagittal multiplanar reformatted images or curved planar reformations enhances the performance of multidetector row computed tomography (�DCT), especially for the evaluation of local extension of pancreatic adenocarcinoma [13][14][15] . It is likely that diagnosis of extrapancreatic neural plexus invasion by pancreatic carcinoma would be more precise and exact using �DCT [16] .…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, carcinomas in the head, uncinate process and tail of pancreas mainly invade the right coelial plexus, superior mesentery artery (��A) nerve plexus and splenic plexus, respectively ��A) nerve plexus and splenic plexus, respectively nerve plexus and splenic plexus, respectively nerve plexus and splenic plexus, respectively [5][6][7]12] . It has been reported that the application of coronal and sagittal multiplanar reformatted images or curved planar reformations enhances the performance of multidetector row computed tomography (�DCT), especially for the evaluation of local extension of pancreatic adenocarcinoma [13][14][15] . It is likely that diagnosis of extrapancreatic neural plexus invasion by pancreatic carcinoma would be more precise and exact using �DCT [16] .…”
Section: Reviewmentioning
confidence: 99%
“…This has led to superior tumor-to-parenchymal enhancement differences, facilitating superior tumor detection and diagnosis, when compared to portal venous (second phase, 70 s delay) or delayed phases (third phase, 150 s delay) of imaging. All the images obtained are used to reconstruct and to observe pancreatic carcinoma and the extrapancreatic invasion [15,16] .…”
Section: Ct Techniquesmentioning
confidence: 99%
“…A curative resection of tumor is the only means of treatment that will hold out a hope of longterm survival for pancreatic cancer patients, although only 10%-15% of them would be eligible for a radical procedure [54] . Preoperative resectability estimation is an outstanding problem of great concern resulting primarily from the intricacies of the involvement evaluation of the major peripancreatic arteries in so far as their actual invasion is regarded as a contraindication to a curative procedure [55][56][57] . Since CT is invariably rated the gold standard for the diagnosis of pancreatic cancer, it is of critical importance that patients with a resectable tumor should not be denied surgery on account of a false-positive CT finding (i.e., when a neoplasm is misinterpreted as nonresectable at CT).…”
Section: Discussionmentioning
confidence: 99%
“…There are several heritable disorders which are associated with an increased incidence of pancreatic ductal adenocarcinoma such as Peutz-Jeghers syndrome (132 times increased risk), hereditary pancreatitis (53 times increased relative risk); familial atypical multiple mole melanoma syndrome (13)(14)(15)(16)(17)(18)(19)(20)(21)(22) times increased risk); familial pancreatic cancer syndrome (9-32 times increased risk) and hereditary breast and ovarian cancer syndrome-BRCA mutation (2-10 times increased risk) [4,5].…”
Section: Epidemiologymentioning
confidence: 99%
“…These images are obtained at either 0.625 mm or 1.25 mm slice thickness. Multiplanar reconstructions in coronal and sagittal planes are performed which greatly enhances identification of secondary signs of tumors and vascular involvement [22].…”
Section: Ctmentioning
confidence: 99%